Arthroscopic Suture-Saucerization of Discoid Meniscus Allows Volume Conservation but Does Not Fully Restore Coverage - Colione Ducrot, M.D; Max Piffoux, Ph.D; Antoine Josse, M.D; Sebastien Raux, M.D; Franck Chotel, M.D., Ph.D (Elsevier, 2023)
Purpose: To quantify the effect of meniscoplasty suture-saucerization on volume and surface coverage of lateral discoid menisci. Methods: This retrospective study included all consecutive 10 patients treated between 2014 and 2019 who had magnetic resonance imaging before and after surgery and 15 controls. The MITK 3M3 semiautomatic software was used to segment the meniscus and cartilage before and after surgery to measure the percentage of meniscus coverage on the tibial cartilage. Results are compared to control patients without knee pathology matched on sex and age with Student t test. Results: Discoid meniscus surface and volume before surgery were respectively 597 mm2 (range, 550-887 mm2) and 2,822 mm³ (1,571-3,407 mm³), representing 74.5% (56%-89%) of the tibial cartilage surface. After surgery, it decreased to 422 mm2 (229-569 mm2) and 1,235 mm³ (680-1,738 mm³), leading to 45.7% (22.5%-68.6%) coverage. In the control group, median surface was 457 mm2 (314-641 mm2), volume was 1,321 mm3 (641-2,240 mm3), and tibial coverage was 55% (41%-77%). Altogether, meniscus volume after surgery was similar to normal, while coverage was significantly lower than controls (P = .04). Conclusions: Meniscoplasty suture-saucerization procedure may allow meniscus sparing and restauration of a similar to normal meniscus volume. Meniscus surface and coverage are diminished compared to controls. Both surface and volume normalization is usually not achievable without decreasing the thickness of the rather thick discoid meniscus. Clinical Relevance: Both surface and volume normalization is usually not achievable without decreasing the thickness of thick discoid menisci.